Marker based enrichment of provitamin A content in two tropical maize synthetics (2021)
Most of the maize (Zea mays L.) varieties in developing countries have low content of micronutrients including vitamin A. As a result, people who are largely dependent on cereal-based diets suffer from health challenges due to micronutrient deficiencies. Marker assisted recurrent selection (MARS), which increases the frequency of favorable alleles with advances in selection cycle, could be used to enhance the provitamin A (PVA) content of maize. This study was carried out to determine changes in levels of PVA carotenoids and genetic diversity in two maize synthetics that were subjected to two cycles of MARS. The two populations, known as HGA and HGB, and their advanced selection cycles (C1 and C2) were evaluated at Ibadan in Nigeria. Selection increased the concentrations of β-carotene, PVA and total carotenoids across cycles in HGA, while in HGB only α-carotene increased with advances in selection cycle. β-cryptoxanthine increased at C1 but decreased at C2 in HGB. The levels of β-carotene, PVA, and total carotenoids increased by 40%, 30% and 36% respectively, in HGA after two cycles of selection. α-carotene and β-cryptoxanthine content improved by 20% and 5%, respectively after two cycles of selection in HGB. MARS caused changes in genetic diversity over selection cycles. Number of effective alleles and observed heterozygosity decreased with selection cycles, while expected heterozygosity increased at C1 and decreased at C2 in HGA. In HGB, number of effective alleles, observed and expected heterozygosity increased at C1 and decreased at C2. In both populations, fixation index increased after two cycle of selections. The greatest part of the genetic variability resides within the population accounting for 86% of the total genetic variance. In general, MARS effectively improved PVA carotenoid content. However, genetic diversity in the two synthetics declined after two cycles of selection.